TENS alleviates CP/CPPS-related inflammation and pain by modulating Kir2.1-dependent macrophage polarization - Hong, Ting; Liu, Xinyu; Chi, Zepai; Liu, Guoyuan; Zhang, Yuanfeng; Lin, Xuanhao; Yao, Peixiu; Gong, Qingyun; Zhang, Yonghai; Hong, Xuwei (Frontiers in Immunology, 2026)
IntroductionChronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) remains a challenging urological condition. This study investigated the therapeutic potential of transcutaneous electrical nerve stimulation (TENS) in experimental autoimmune prostatitis (EAP) and explored its underlying mechanisms.MethodsProstate tissue samples from 26 benign prostatic hyperplasia (BPH) patients were collected at Shantou Central Hospital and analyzed for M1/M2 macrophage infiltration using immunohistochemistry (IHC). In animal experiments, 24 male Sprague–Dawley rats were divided into control (n = 4), EAP (n = 7), and TENS treatment groups (n = 13; EAP + 1 Hz, n = 3; EAP + 2 Hz, n = 3; EAP + 4 Hz, n = 7). EAP was induced via prostate antigen injections, and TENS (1–4 Hz) was applied. In cell experiments, RAW264.7 macrophages were grouped into control, LPS-stimulated, electrical stimulation (ES)-treated (0.1–0.5 V/cm), and ES + pharmacological intervention (zacopride/probenecid) groups to study repolarization mechanisms.ResultsIn BPH tissues, the M1/M2 macrophage ratio positively correlated with inflammation severity. In EAP rats, 4 Hz TENS significantly alleviated pelvic pain, reduced proinflammatory cytokine expression, and reversed histopathological damage. TENS promoted macrophage repolarization toward the M2 phenotype. ES in vitro similarly induced M1-to-M2 repolarization, which was associated with decreased inwardly rectifying K+ channel Kir2.1 (Kir2.1) and Transient receptor potential vanilloid 2 (TRPV2) expression, membrane depolarization, reduced Ca2+ influx, and a shift from NF-κB/STAT1 to STAT6 signaling. Agonists of Kir2.1 TRPV2 reversed these effects.ConclusionTENS alleviates CP/CPPS by promoting M1-to-M2 macrophage repolarization, representing a promising therapeutic strategy.